Pediatric and adolescent cancer disparities in the Middle East and North Africa (MENA) region: incidence, mortality, and survival across socioeconomic strata - Ankita Shukla; Rouba Karen Zeidan; Basema Saddik (BMC Public Health)
Abstract Background Cancer is one of the leading causes of death in children and adolescents, with a significant concentration in low and middle-income countries. Previous research has identified disparities in cancer incidence and mortality based on a country’s level of development. The Middle East and North Africa (MENA) region comprises of countries with heterogeneous income and development levels. This study aims to investigate whether discrepancies in cancer incidence and mortality among children and adolescents exist in countries within the MENA region. Materials and methods Data on cancer incidence and mortality were drawn from the Global Burden of Disease Study (GBD) 2019 for all malignant neoplasms (including non-melanoma skin cancers). The analysis was restricted to children and adolescents aged less than 20 years. Mortality- to-Incidence ratios (MIR) were calculated as a proxy measure of survival for each cancer type and country and Spearman’s correlation coefficient measured the association between socio-demographic index (SDI), incidence rates, mortality rates, and MIR. Results In 2019, cancer incidence in the MENA region was 4.82/100,000 population, while mortality rate was 11.65/100,000 population. Cancer incidence and mortality was higher among males compared to females. A marked difference was observed in cancer-related mortality rates between low-income and high-income countries. MIR was higher in low-income countries, particularly for males and specific cancer types such as liver, colon and rectum, brain and central nervous system (CNS) cancers, and non-Hodgkin lymphoma among others. A negative correlation was observed between a country’s SDI and MIR (-0.797) and SDI and mortality rates (-0.547) indicating that higher SDI corresponds to lower MIR and lower mortality rates. Conclusion These findings highlight the need for evidence-based interventions to reduce cancer-related mortality and disease burden among children and adolescents, particularly in low-income countries within the region and for cancer types with the highest mortality rates. Additionally, efforts should focus on establishing registries to provide up-to-date national data on cancer incidence and mortality in countries within the region.